2015
DOI: 10.1021/acsnano.5b05974
|View full text |Cite
|
Sign up to set email alerts
|

Trimodal Therapy: Combining Hyperthermia with Repurposed Bexarotene and Ultrasound for Treating Liver Cancer

Abstract: Repurposing of existing cancer drugs to overcome their physical limitations, such as insolubility, represents an attractive strategy to achieve enhanced therapeutic efficacy and broaden the range of clinical applications. Such an approach also promises to offer substantial cost savings in drug development efforts. Here we use repurposed FDA-approved topical agent bexarotene (Targretin™), currently in limited use for cutaneous manifestations of T-cell lymphomas, and re-engineer it for use in solid tumor applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 65 publications
0
39
0
Order By: Relevance
“…5 A-D). The results obtained from 3-(4′,5′-dimethylthiazol-2′-yl)-2,5-diphenyltetrazolium bromide (MTT) assay (49) suggested that 5 was effective in Cur-regulated cell growth inhibition of all used cancer cell lines. Moreover, the growth inhibition efficiency was significantly improved in these cells, as supported by the decrease of IC 50 values to a biostatistically significant level of P < 0.0001 (SI Appendix, Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…5 A-D). The results obtained from 3-(4′,5′-dimethylthiazol-2′-yl)-2,5-diphenyltetrazolium bromide (MTT) assay (49) suggested that 5 was effective in Cur-regulated cell growth inhibition of all used cancer cell lines. Moreover, the growth inhibition efficiency was significantly improved in these cells, as supported by the decrease of IC 50 values to a biostatistically significant level of P < 0.0001 (SI Appendix, Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Typical therapeutic treatments still experience impeded target specicity, poor bioavailability and organ toxicity. 1,2 To improve the pharmacological properties and bioavailability of many drugs, drug-delivery systems are introduced to release a controlled amount of drug at the intended target sites. 3 In the eld of medicine, nanotechnology has played a revolutionary role in which nanostructures are used to deliver drugs to specic disease-centred cells.…”
Section: Introductionmentioning
confidence: 99%
“…[53] Briefly, ≈80% confluent MCF-7 cells were treated for 72 h with Nic formulations. At the end of the incubation period, cells were washed, spun and collected in 400 μL of lysis buffer.…”
Section: Methodsmentioning
confidence: 99%